Antidiabetic and hepatoprotection effect of butterfly pea flower (Clitoria ternatea L.) through antioxidant, anti-inflammatory, lower LDH, ACP, AST, and ALT on diabetes mellitus and dyslipidemia rat - Wahyu Widowati; Lusiana Darsono; Herry S. Utomo; Adilah Hafizha Nur Sabrina; Maria Rizka Natariza; Albert Christoper Valentinus Tarigan; Novaldo Wahid Waluyo; Abigail Maydaline Gleyriena; Berlian Haifa Siahaan; Reza Oktaviani (Heliyon, 2024)
This study explores the antidiabetic and hepatoprotective potential of Butterfly pea flower extract (Clitoria ternatea L.) (CTE) in diabetic and dyslipidemia rat models. Diabetes Mellitus (DM) is a chronic metabolic disorder marked by high levels of blood glucose, which can cause dyslipidemia and liver damage as a result of oxidative stress. CTE, a natural substance, is recognized for its positive attributes, such as anti-inflammatory, antioxidant, anti-diabetic, anti-dyslipidemia, antibiotic, and liver tissue protection capabilities. Dyslipidemia was induced in rats using a high-fat diet (HFD) and propylthiouracil (PTU) for 28 days. DM was induced using streptozotocin (STZ) and nicotinamide (NA). Rats were treated with varying doses of CTE for 28 days, along with glibenclamide and simvastatin. The research showed that CTE raised the levels of SOD, CAT, and liver proteins while lowering the levels of MDA, LDH, ACP, AST, ALT, IL-1β, and CRP in rats with DM and dyslipidemia. This suggests that CTE might be useful for treating DM.